Mortality reduction from quitting smoking in Hong Kong: population-wide proportional mortality study. (8th February 2018) - Mai, Zhi-Ming; Ho, Sai-Yin; Lo, Ching-Man; Wang, Man-Ping; Peto, Richard; Lam, Tai-Hing
Abstract: Background: The effects of smoking cessation might be different in different populations. Proportional mortality studies of all deaths, relating the certified cause to retrospectively determined smoking habits, have helped assess the hazards of smoking in Hong Kong, and further analyses can help assess the effects of prolonged cessation (although not of recent cessation, as life-threatening disease can itself cause cessation, particularly in old age). Methods: The LIMOR study sought the certified causes of all deaths in 1998, and interviewed 81% of families at death registries to determine the decedent's smoking history. Cases were deaths from pre-defined diseases of interest ( N = 15 356); controls were deaths from pre-defined non-smoking-related diseases ( N = 5023). Case vs control odds ratios for ex-smokers vs smokers were calculated by age-, sex- and education-standardized logistic regression. These are described as mortality rate ratios (RRs), with a group-specific confidence interval (CI). Results: For the aggregate of all deaths from any of the diseases of interest at ages 35-69 years, the RRs for current smoking, quitting 0-4, 5-9 or 10+ years ago and never-smoking were, respectively, RR = 1 (95% CI 0.86-1.17), 0.91 (0.73-1.14), 0.71 (0.49-1.02), 0.66 (0.50-0.87) and 0.43 (0.37-0.48). Younger age of quitting (25-44 or 45-64) appeared to be associated with greater protection: RR = 0.58 (0.38-0.88) and 0.71 (0.54-0.93), respectively. These patterns were less clear at older ages, particularly for death from emphysema. Conclusions: Longer durations of smoking cessation are associated with progressively lower mortality rates from the diseases of interest. For sustainable monitoring of tobacco-attributed mortality, approximate years since last smoked should be recorded during death registration.